Post-cesarean section laparoscopic cholecystectomy: a case report - Sarah Magdy Abdelmohsen; Mohamed Mahmoud Zidan; Sherif Salah Eldeen Fahmy; Ahmed Saleh Baghdady (BMC, 2023)
Abstract Background Laparoscopic cholecystectomy at the time of cesarean section is novel in medicine. It is safe, feasible, and cost-effective. Case presentation A 29-year-old G3P2 + 0 woman had two previous cesarean sections. She was pregnant at 32 weeks. The fetus had anencephaly. She had acute cholecystitis. Laparoscopic cholecystectomy done at the time of termination of pregnancy by cesarean section. Conclusions In a critical period, such as acute cholecystitis, the combination of laparoscopic cholecystectomy immediately post cesarean section is effective if the surgeon is highly qualified and experienced.